Priorities for research on meningococcal disease and the impact of serogroup A vaccination in the African meningitis belt - (:unkn) unknown (My University, 2013)
For over 100 years, large epidemics of meningococcal meningitis have occurred every few years in areas of the African Sahel and sub-Sahel known as the African meningitis belt. Until recently, the main approach to the control of these epidemics has been reactive vaccination with a polysaccharide vaccine after an outbreak has reached a defined threshold and provision of easy access to effective treatment but this approach has not prevented the occurrence of new epidemics. Meningococcal conjugate vaccines, which can prevent meningococcal carriage and thus interrupt transmission, may be more effective than polysaccharide vaccines at preventing epidemics. Because the majority of African epidemics have been caused by serogroup A meningococci, a serogroup A polysaccharide/tetanus toxoid protein conjugate vaccine (PsA-TT) has recently been developed. Results from an initial evaluation of the impact of this vaccine on meningococcal disease and meningococcal carriage in Burkina Faso have been encouraging. To review how the research agenda for meningococcal disease in Africa has been changed by the advent of PsA-TT and to define a new set of research priorities for study of meningococcal infection in Africa, a meeting of 41 scientists was held in Dakar, Senegal on April 24th and 25th 2012. The research recommendations developed during the course of this meeting are presented in this paper. The need for enhanced surveillance for meningitis in defined populations with good diagnostic facilities in African countries at risk of epidemics was identified as the highest priority. This is needed to determine the duration of protection against serogroup A meningococcal disease provided by PsA-TT and to determine the risk of disease and carriage caused by meningococci of other serogroups. Other research areas given high priority included identification and validation of serological correlates of protection against meningococcal disease and carriage, development of improved
Keywords: African Research